2021
DOI: 10.1177/07067437211000636
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence and Comorbidity of Mental Disorders in the Two-wave 2002–2018 Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey (CAFVMHS): Prévalence et Comorbidité de Durée de vie Des Troubles Mentaux Dans l’Enquête de Suivi Sur la Santé Mentale Auprès des Membres des Forces Armées Canadiennes et Des ex-Militaires (ESSMFACM) en Deux Cycles de 2002 à 2018

Abstract: Objective: The current study used the Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey (CAFVMHS) to (1) examine the incidence and prevalence of mental disorders and (2) estimate the comorbidity of mental disorders over the follow-up period. Method: The CAFVMHS (2018) is a longitudinal study with two time points of assessment. The sample is comprised of 2,941 Canadian Forces members and veterans who participated in the 2002 Canadian Community Health Survey: Canadian Forces Supplement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Our reported rates of probable PTSD and probable MDD rates were higher than previously reported norms (34% and 35%, respectively, compared to 15% and 18% in 2013) (Richardson et al, 2014 ; Thériault et al, 2020 ). However, findings are consistent with similarly high rates of lifetime prevalence for mental health conditions self-reported in the CAF Members and Veterans Mental Health Follow-up Survey (Sareen et al, 2021 ). These rates, in part, may be attributable to the negative impact of social isolation on the already-vulnerable population of Veterans with high prevalence of mental health conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Our reported rates of probable PTSD and probable MDD rates were higher than previously reported norms (34% and 35%, respectively, compared to 15% and 18% in 2013) (Richardson et al, 2014 ; Thériault et al, 2020 ). However, findings are consistent with similarly high rates of lifetime prevalence for mental health conditions self-reported in the CAF Members and Veterans Mental Health Follow-up Survey (Sareen et al, 2021 ). These rates, in part, may be attributable to the negative impact of social isolation on the already-vulnerable population of Veterans with high prevalence of mental health conditions.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, individuals with a PTSD diagnosis displayed significantly elevated depressive symptoms compared to healthy controls. This is certainly in line with previous reports revealing that among those with a diagnosis of PTSD, 79.6% will also experience a major depressive episode in their lifetime (Sareen et al, 2021). Additionally, it was found that individuals with the dissociative PTSD subtype displayed elevated negative affect and depression scores, with a mean BDI score that met the cut-off for severe depression, compared to individuals with non-dissociative PTSD.…”
Section: Symptom Profiles and Heterogeneitysupporting
confidence: 91%
“…Due to the elevated levels of trauma experienced, veterans and military personnel are at risk of not only developing PTSD, but also co-occurring mental disorders. In line with this suggestion, of the veterans with a PTSD diagnosis, approximately 80% also had major depressive episodes, 46% had a generalized anxiety disorder, 51% had a panic disorder, and 59% had a social anxiety disorder (Sareen et al, 2021). These findings suggest that over time, mental disorders may accumulate, even long after the exposure to trauma.…”
Section: Trauma Exposure Among Veteransmentioning
confidence: 52%
“…First responders, such as firefighters, police officers, and paramedics, are often exposed to potentially traumatic events as part of their occupation. As a result, they experience higher rates of mental and physical health issues compared to the general population (Fullerton, Ursano, & Wang, 2004;Hourani et al, 2020;Jones, 2017;Pedersen, Ugelvig Petersen, Ebbehøj, Bonde, & Hansen, 2018;Sareen et al, 2021;Wright et al, 2021). Notably, first responders are at an increased risk of post-traumatic stress disorder (PTSD), which often co-occurs with depressive symptoms, suicidal thoughts, and related behaviours (Jones, 2017;Lewis-Schroeder et al, 2018;Stanley, Hom, & Joiner, 2016).…”
Section: Introductionmentioning
confidence: 99%